Bioconcentration of heavy metals in aquatic macrophytes of South Urals region lakes - TATYANA G. KRUPNOVA; IRINA V. MASHKOVA; ANASTASIYA M. KOSTRYUKOVA; NIKITA O. EGOROV; SVETLANA V. GAVRILKINA (Biodiversitas Journal of Biological Diversity, 2018)
Krupnova TG, Mashkova IV, Kostryukova AM, Egorov NO, Gavrilkina SV. 2018. Bioconcentration of heavy metals in aquatic macrophytes of South Urals region lakes. Biodiversitas 19: 296-302. This paper studies bioconcentration of heavy metals in macrophytes. High concentration of heavy metal compounds in the lakes of South Ural is natural. Moreover, some of the South Ural lakes are polluted by heavy metals that get into the water together with partly treated sewage of ferrous and non-ferrous industries as well as mining. The paper analyzes similarities and differences of macrophyte communities in six lakes: Bolshoye Miassovo, Bolshoy Ishkul, Bolshoy Tatkul, Argayash, Savelkul, Baraus. In our research, we determined species diversity for each lake. Potamogeton lucens L. and Lemna minor L. were found in all the studied lakes, and the concentrations of heavy metals were studied in their leaves. Such metals as Fe, Mn, Cu, Zn were found in macrophytes. We obtained a metal ratio Mn <Fe<Cu<Zn in plant leaves. High accumulation of Fe, Cu, Zn was observed in Lemna while Mn accumulates equally. Metals bioconcentration factors (BCFs) were calculated